(untitled) (Journal of Informatics Education and Research, 2023)
Business and customers are online now for number of reasons like ease of doing things, time saving, better information, better products and services and discounts. Consequently marketing is also done on social media platforms like Facebook, Instagram, youtube, twitter and snap chat. This trend of promoting business is rising and offline businesses have also started engaging in promoting business through social media platforms. The objective of this study is to present a bibliometric analysis of social media as a marketing platform based on scopus database for a limited time period. In doing so, this study unpacks the most influential articles and top contributing journals, authors, institutions, and countries, as well as the methodological choices and research contexts for social media as a marketing platform.